Adolescents and young adults with oncohematological disease: use of social networks, impact of SARS-COV-2, and psychosocial well-being - Tremolada, Marta; Taverna, Livia; Vietina, Francesco; Incardona, Roberta Maria; Pierobon, Marta; Bonichini, Sabrina; Biffi, Alessandra; Bisogno, Gianni (Frontiers in Psychiatry, 2023)
Objective Adolescents and young adults (AYA) with oncohematological diseases could have important psychosocial difficulties that could be worsened by the effects of the COVID19 pandemic. At this developmental stage, it is also important to assess the use of social networks (SNs). This study aims to investigate the type of social network use and the consequences of the COVID19 period. These patients are compared with matched healthy peers. Methods After the informant consent signature, the adolescents completed a series of self-report questionnaires on the use of SNs, on communication preferences, on social anxiety and on Covid19 impact through the online platform of LimeSurvey. Most of the adolescents belonged to the 18–20 age group (42.5%), were female (62%) and mainly off therapy (72%). Results Adolescents spent more than 2 h/day on Instagram and 1 h and half on Whatsapp, while Tik Tok use was on average 1 h/day, especially used by younger patients (r = −0.33, p = 0.023). Males used Twitch (t45 = −2.06, p = 0.05) and Youtube (t45 = −2.18, p = 0.03) for longer than females. AYA in therapy used more Tik Tok (U = 137.50; p = 0.03), Ask/Tellonym (U = 172.50; p = 0.05) and Twitch (U = 144; p = 0.017) than those off therapy. Healthy AYA showed lower levels of exposure (Z = −4.17; p = 0.00001) and impact (Z = −5.12; p = 0.00001) to Covid19, while the level of social anxiety is comparable and is in the normal range in both groups. Discussion Some clinical considerations and suggestions could be given based on these empirical results to health professionals in the care of AYA cancer patients.